Disruption of cerebellar microzonal organization in GluD2 (GluRδ2) knockout mouse - Hashizume, Miki; Miyazaki, Taisuke; Sakimura, Kenji; Watanabe, Masahiko; Kitamura, Kazuo; Kano, Masanobu (Frontiers in Neural Circuits, 2013)
Cerebellar cortex has an elaborate rostrocaudal organization comprised of numerous microzones. Purkinje cells (PCs) in the same microzone show synchronous activity of complex spikes (CSs) evoked by excitatory inputs from climbing fibers (CFs) that arise from neurons in the inferior olive (IO). The synchronous CS activity is considered to depend on electrical coupling among IO neurons and anatomical organization of the olivo-cerebellar projection. To determine how the CF–PC wiring contributes to the formation of microzone, we examined the synchronous CS activities between neighboring PCs in the glutamate receptor δ2 knockout (GluD2 KO) mouse in which exuberant surplus CFs make ectopic innervations onto distal dendrites of PCs. We performed in vivo two-photon calcium imaging for PC populations to detect CF inputs. Neighboring PCs in GluD2 KO mice showed higher synchrony of calcium transients than those in wild-type (control) mice. Moreover, the synchrony in GluD2 KO mice hardly declined with mediolateral separation between PCs up to ~200 µm, which was in marked contrast to the falloff of the synchrony in control mice. The enhanced synchrony was only partially affected by the blockade of gap junctional coupling. On the other hand, transverse CF collaterals in GluD2 KO mice extended beyond the border of microzone and formed locally clustered ectopic synapses onto dendrites of neighboring PCs. Furthermore, PCs in GluD2 KO mice exhibited clustered firing (Cf), the characteristic CF response that was not found in PCs of wild-type mice. Importantly, Cf was often associated with localized calcium transients in distal dendrites of PCs, which are likely to contribute to the enhanced synchrony of calcium signals in GluD2 KO mice. Thus, our results indicate that CF signals in GluD2 KO mice propagate across multiple microzones, and that proper formation of longitudinal olivo-cerebellar projection is essential for the spatiotemporal organization of CS activity in the cerebellum.